2015
DOI: 10.1260/0144-5987.33.1.91
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Trace Element Concentrations and Coal-Forming Environments in the No. 6 Coal Seam, Haerwusu Mine, China

Abstract: In order to study the relationship between trace element concentrations and coalforming environment in the No. 6 Coal, Haerwusu Mine, Inner Mongolia, China, 39 bench samples were taken from the opencast mine, following Chinese Standard Method GB/T 482-2008. The samples were analyzed by an optical microscope, a scanning electron microscope in conjunction with an energy-dispersive X-ray spectrometer (SEM-EDX) analysis, inductively coupled plasma mass spectrometric (ICP-MS). The results indicate that the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Most of these studies focused on the anomalous concentration of trace elements in coals and the affinity of these elements to the organic matters or the inorganic parts can be discerned on the level of mineral (Chu et al, 2015;Kang et al, 2014). However, the studies on the enrichment mechanisms and the origin of these elements in coals are scared (Qin et al, 2015b) and badly needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies focused on the anomalous concentration of trace elements in coals and the affinity of these elements to the organic matters or the inorganic parts can be discerned on the level of mineral (Chu et al, 2015;Kang et al, 2014). However, the studies on the enrichment mechanisms and the origin of these elements in coals are scared (Qin et al, 2015b) and badly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a variety of trace elements including Li, Ge, U, Hg is reported to be enriched in coal seams worldwide (Dai et al., 2014; Qin et al., 2015a, 2015b; Seredin et al., 2013; Sun, 2015; Sun et al., 2012, 2013a, 2013b, 2016). Most of these studies focused on the anomalous concentration of trace elements in coals and the affinity of these elements to the organic matters or the inorganic parts can be discerned on the level of mineral (Chu et al., 2015; Kang et al., 2014). However, the studies on the enrichment mechanisms and the origin of these elements in coals are scared (Qin et al., 2015b) and badly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Datong coalfield is one of the most important coal-producing areas in China, and studies have been carried out on the mineralogy and geochemistry from the Carboniferous and Permian coals in, and adjacent to, the Datong coalfield [7,9,10,[16][17][18]20,[26][27][28]. Findings from these studies have shown that the sediment source is dominated by both Cambrian-Ordovician strata as well as Archean metamorphic rocks [9,10,[16][17][18]20,[26][27][28][29]. Additionally, the low temperature hydrothermal solution activities in this area have significantly influenced the abundance and modes of occurrence of trace elements present in the coal.…”
Section: Introductionmentioning
confidence: 99%
“…The valuable trace elements associated with Jungar coal have been reported by many authors [1,[6][7][8][9][10][11][12], and the toxic trace elements have been investigated by several researchers [13][14][15][16]. However, these previous studies were essentially focused on the northern and central parts of the Jungar Coalfield, such as the Heidaigou Opencut Mine, the Haerwusu Opencut Mine, and the Guanbanwusu Mine (Figure 1) [4,5,7,17,18].…”
Section: Introductionmentioning
confidence: 99%